Surface morphology of cadmium telluride films prepared by vacuum sputtering on the silicon and cadmium telluride substrates - Akobirova, Aziza T.; Halauchyk, Victoryia I.; Lukashevich, Michail G.; Sultonov, Nizom S.; Hamroqulov, Rajabmurod B. (Journal of the Belarusian State University. Physics, 2017)
The results of atomic-force and scan electron microscopy of cadmium telluride films prepared on silicon and monocrystall in cadmium telluride substrates by means of sputtering in quasi-closed volume are presented. It is shown that mean grain size of the obtained films ranging in the interval 2.5–5.0 µm with roughness of the films changing in the range 34,1–87,5 nm. Etching of films bromine-butyl etchant results in improved surface morphology and roughness of the film reduces to 17.9 nm. The elemental composition of the film surface layer was determined by X-ray microanalysis and structure by X-ray diffractometer.